A N-heterocyclic tetracarbene Pd(ii) moiety containing a Pd(ii)–Pb(ii) bimetallic MOF for three-component cyclotrimerization via benzyne. Issue 69 (4th August 2016) - Dong, Ying; Li, Yue; Wei, Yong-Liang; Wang, Jian-Cheng; Ma, Jian-Ping; Ji, Jun; Yao, Bing-Jian; Dong, Yu-Bin
Abstract : A N-heterocyclic tetracarbene Pd(ii ) moiety containing a bimetallic metal–organic framework Pd(ii )–Pb(ii )–MOF, which can be a highly active heterogeneous catalyst for three-component cyclotrimerization, is reported. Abstract : A novel Pd(ii )–Pb(ii ) bimetallic metal–organic framework Pd(ii )–Pb(ii )–MOF (B) which contains an N-heterocyclic tetracarbene Pd(ii ) moiety was synthesized based on a chelating N-heterocyclic dicarbene Pd(ii )–NHDC ligand (A) under solvothermal conditions. It can be a highly active heterogeneous catalyst for three-component cyclotrimerization via benzyne species.